Parenting styles, empathy and aggressive behavior in preschool children: an examination of mediating mechanisms - Lin, Zhumei; Zhou, Ziqian; Zhu, Lijun; Wu, Weige (Frontiers in Psychology, 2023)
This study examined the interplay between parenting styles, empathy, and aggressive behavior in Chinese preschool children aged 3-5 years. Data were collected from 87 participants using the Child Behavior Checklist, Children's Empathy Quotient, and Parenting Style Questionnaire, and were subsequently analyzed. The findings revealed significant age and gender differences in empathy, but not in parenting styles or aggressive behavior. Additionally, a substantial correlation was identified between authoritarian parenting style and aggressive behavior, as well as between children's empathy levels and aggressive behavior. This indicates that empathy may act as a mediator between parenting style and aggressive behavior. Specifically, our findings suggest that an authoritarian parenting style influences aggressive behavior both directly and indirectly through its effect on children's empathy. These results point towards the possibility that an authoritarian parenting style may stifle the development of empathy in preschool children, subsequently heightening their aggressive behavior.Existing research has highlighted connections between parenting styles, empathy, and aggressive behavior but has yielded inconsistent results and lacks clarity on the mediating mechanisms underlying these relationships. Furthermore, prior studies have predominantly focused on adolescents, leaving a research gap concerning younger children. No studies to date have delved into the intricate interrelationships between these three factors in a preschool population. Given that parental behaviors exert a profound impact during early childhood, understanding these dynamics provides an opportunity to modify the trajectory of potential conduct issues. Hence, by examining a preschool sample, this study aims to shed light on the interplay between parenting styles, aggressive behavior, and empathy, potentially offering a valuable reference for comprehending the mechanisms that underlie the formation of children's aggressive behavior.